STEEL COLUMNS FINITE ELEMENT BUCKLING ANALYSIS BY OPEN-SOURCE SOFTWARE FreeCAD. (REMUNOM, 2025)
Steel structures are widely used in buildings that demand rapidity and large free spans, because they are slender, lighter and stronger than concrete structures. This slenderness, however, make these structures prone to buckling, an instability phenomena characterized by columns repentine curvature. In cold-formed structures, there are also local and distortional buckling due to the use o very thin steel plates, that makes, their behavior still more complex. Numerical melhods, as the Finite Element Method, are commonly used to evaluate the strenght and behavior of steel structures. There are commercial Finite Element packages, but their high costs may difficult access by institutions and professionals tho them. An alternative are the open-source software, as FreeCAD. This work analyses the efficience of steel columns bucking analysis by FreeCAD Finite Element workbench. Laminated and cold-formed columns were analized, and Finite Element results were compared to theoretical ones. It was observed good agreement of results. It validades the procedures developed in buckling Finite Element analysis by FreeCAD. That indicates a possibility of costs reduction for institutions and professionals by adoption of FreeCAD for steel structuresfor research and design.